Information and Communications Technology in Dentistry: an informative and educational approach for patients with fixed orthodontic appliances - Marina Araújo Leite ASSIS; Lílian Dayse Fróes TAVARES; Aline Pereira BERNARDINO; Breno Amaral ROCHA; Lucas Guimarães ABREU; Dauro Douglas OLIVEIRA; Matheus Melo PITHON; Rodrigo Villamarim SOARES (Dental Press Journal of Orthodontics, 2022)
ABSTRACT Objective: To develop and make available, at no cost to the user, Information and Communications Technology (ICT) tools for Dentistry, providing dental information and advice geared toward patients undergoing orthodontic treatment with fixed appliances. Material and Methods: A Dentistry-based content that contemplated information and advice concerning orthodontic treatment with fixed appliances was elaborated. The materials, which included instructions on oral hygiene and treatment strategies when faced with possible complications, were evaluated and validated by specialists, whose assessments reached a 85% approval. From the validated content, products using four distinct ICT tools were formulated. Results: The following technological products were developed: a program for community radios, three blog posts, four educational and informative videos, and a smartphone application - using texts, as well as images and videos. These ICT tools, geared toward patients wearing fixed orthodontic appliances, were made available by internet at no cost to the user, and the number of accesses is already expressive. Conclusion: These technological-scientific tools, developed and provided freely to the population, can aid patients during their treatment with fixed orthodontic appliances, contributing to the dissemination of reliable information, and clarifying doubts that may arise during orthodontic therapy. These free ICT tools serve to facilitate access to scientific knowledge, thereby favoring social inclusion, bearing in mind that this educational and informative material was offered in a simple and accessible manner to the general population.